2014
DOI: 10.3892/mco.2014.330
|View full text |Cite
|
Sign up to set email alerts
|

Health resource utilisation associated with skeletal-related events in European patients with lung cancer: Α subgroup analysis from a prospective multinational study

Abstract: Abstract. Bone complications or skeletal-related events (SREs), typically defined as radiation to bone, pathological fractures, surgery to bone and spinal cord compression, occur frequently in patients with bone metastases. As the survival of patients with advanced lung cancer improves, preventing SREs is becoming increasingly clinically relevant. The aim of this analysis was to assess the impact of SREs on health resource utilisation (HRU) in European lung cancer patients with bone metastasis. This multinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
3
10
0
2
Order By: Relevance
“…This is a smaller proportion than in patients with other cancer types (lung cancer, 80%; prostate cancer, 74%; breast cancer, 58%). [14][15][16] The reasons for this difference are unclear and are beyond the scope of this study, but a speculative explanation could be that the threshold to initiate imag- Outpatient visits were necessary for the majority of SREs (63.7%) and were most frequently required for radiation to bone (74.8%) and vertebral fracture (73.3%). In the UK, the mean number of outpatient visits required per SRE was less than one-third of that of the overall mean.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is a smaller proportion than in patients with other cancer types (lung cancer, 80%; prostate cancer, 74%; breast cancer, 58%). [14][15][16] The reasons for this difference are unclear and are beyond the scope of this study, but a speculative explanation could be that the threshold to initiate imag- Outpatient visits were necessary for the majority of SREs (63.7%) and were most frequently required for radiation to bone (74.8%) and vertebral fracture (73.3%). In the UK, the mean number of outpatient visits required per SRE was less than one-third of that of the overall mean.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, the data presented here indicate that outpatient visits impose a considerable burden on healthcare resources in Europe, similar to findings reported for other cancer types in this study. 3,[14][15][16] This study has identified that almost every SRE required a procedure, and multiple procedures were common. Overall, a mean of 7.4 procedures per SRE was required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two classes of medications, the RANK-ligand inhibitors and bisphosphonates, reduce the number of skeletal events, such as pathologic fracture, in patients with metastatic disease to bone. [23][24][25][26] However, most of those studies focused on the 3 most common carcinomas (breast, lung, and prostate) to metastasize to bone and cause pathologic fracture. ere is greater variability in the prophylactic treatment of other forms of cancer that have metastasized to bone amongst oncologists.…”
Section: Discussionmentioning
confidence: 99%
“…26 In a European study in lung cancer patients with at least 1 SRE, 41% of the events required hospitalization during a median of 19 days. 27 In several studies from Germany, 28 Spain, 28,29 Italy, 28 the United Kingdom, 28 Portugal, 30 and Belgium, 31 costs of each SRE were in the following ranges: pathologic fractures: V4712 to V8730; radiation to bone, V1485 to V3877; spinal cord compression: V7903 to V13,203; and surgery to bone: V3348 to V12,092. In a French study of 554 lung cancer patients with bone metastasis, 49.5% of yearly costs related to bone metastasis could be assigned to SREs.…”
mentioning
confidence: 99%